2023
DOI: 10.1093/jxb/erad253
|View full text |Cite
|
Sign up to set email alerts
|

Light-mediated anthocyanin biosynthesis in rose petals involves a balanced regulatory module comprising transcription factors RhHY5, RhMYB114a, and RhMYB3b

Abstract: Roses are significant botanical species with both ornamental and economic value, displaying diverse floral traits, particularly an extensive array of petal colors. The red pigmentation of rose petals is predominantly attributed to anthocyanin accumulation. However, the underlying regulatory mechanism of anthocyanin biosynthesis in roses remains elusive. This study presents a novel light-responsive regulatory module governing anthocyanin biosynthesis in rose petals, which involves the transcription factors RhHY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…Previous studies have reported that S6 subgroup of MYB involved in anthocyanin accumulation, contained 5 genes ( RcMYB113a , RcMYB113b , RcMYB113c , RcMYB114a and RcMYB114b ) (Li et al, 2021 ). Three of them ( MYB113a, RcMYB11 3c called RcMYB114 in previous reports, and RcMYB114a ), have been reported (Lin-Wang et al, 2010 ; Li et al 2022 , Yan et al 2023 ). In our study, another new gene RcMYB114b was identified .…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Previous studies have reported that S6 subgroup of MYB involved in anthocyanin accumulation, contained 5 genes ( RcMYB113a , RcMYB113b , RcMYB113c , RcMYB114a and RcMYB114b ) (Li et al, 2021 ). Three of them ( MYB113a, RcMYB11 3c called RcMYB114 in previous reports, and RcMYB114a ), have been reported (Lin-Wang et al, 2010 ; Li et al 2022 , Yan et al 2023 ). In our study, another new gene RcMYB114b was identified .…”
Section: Discussionmentioning
confidence: 94%
“…The expression of RcMYB114a was up-regulated at the flower in early opening stage and highest at the fully open flower stage, whereas the expression of RcMYB114b was highest at the flower in early opening stage and down-regulated at the fully open flower stage. Different from above, RcMYB11 3c was largely unexpressed (Yan et al 2023 ). In addition, different expression patterns of homologous genes were also found in strawberry, which may affect fruit color (Lin-Wang et al, 2010 ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Similarly, LhMYB18 interacted with LhbHLH2 to activate the promoter of DFR, which was responsible for large spot formation in an Asiatic hybrid lily cultivar [19], while HaMYB1 modulated UFGT to promote anthocyanin accumulation in Helianthus annuus [48]. Recently, RcMYB1 [49], RhMYB114a [50], RhMYB3b [50], and Rosa1 [51] were shown to play roles in anthocyanin synthesis in roses. In this study, three MYBs and one MYB-related TF were highly associated with anthocyanins in R. persica.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, two R2R3-MYBs (DPL and PHZ) regulate the pigmentation pattern of flowers, and transcripts for PHZ are induced by high light in petunias [54]. In turn, light-responsive RhHY5 positively activates the expression of RhMYB114a and represses the expression of RhMYB3b to regulate anthocyanin biosynthesis in rose petals [50]. The overexpression of a C2H2-type zinc finger protein gene MdZAT5 in apple calli and Arabidopsis enhances anthocyanin accumulation [55].…”
Section: Discussionmentioning
confidence: 99%